2021
DOI: 10.1007/s10067-021-05759-8
|View full text |Cite
|
Sign up to set email alerts
|

Ability and willingness to utilize telemedicine among rheumatology patients—a cross-sectional survey

Abstract: Introduction/objectives This study aims to assess the patients’ ability and willingness to utilize telemedicine (TM) along with identifying some of the barriers to a more widespread adoption of TM in rheumatology. Methods An observational, cross-sectional study of patients visiting a rheumatology clinic was conducted in 2018. We used a survey to assess patients’ attitude on the perceived effectiveness when comparing TM versus in-person visits, as well as patients’ acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The younger groups tend to be more familiar with the newer technology, which results in them being more aware of the newer services that have been offered. In another study that was conducted in the United States, older people were not likely to be interested in using telemedicine services due to their lack of belief that the health care purpose can be achieved at a distance ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The younger groups tend to be more familiar with the newer technology, which results in them being more aware of the newer services that have been offered. In another study that was conducted in the United States, older people were not likely to be interested in using telemedicine services due to their lack of belief that the health care purpose can be achieved at a distance ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Before the pandemic, home-based automated systems and web-based services were developed to encompass telemonitoring, teleconsulting, and tele-education for patients with IBD [ 104 ], with patient acceptance of virtual monitoring increasing in rheumatology and gastroenterology settings [ 104 , 105 ]. One systematic review found telerheumatology to be met with high rates of patient satisfaction [ 106 ], although potential barriers, such as accessibility and acceptance of telemedicine by older patients, must be considered [ 107 ]. Indeed, rheumatology patients receiving SC biologics have been managed successfully via telemedicine during the pandemic [ 2 , 108 ].…”
Section: Clinical Implications Of Sc Infliximab In the Covid-19 Pandemic Era And Beyondmentioning
confidence: 99%
“…A video connection could also be used in combination with patient portals and access to EHRs [ 42 ] and different devices and apps [ 125 ]. Video consultations offer possibilities for first and follow-up visits at the clinic [ 46 , 49 , 53 ], for peri- and postoperative sessions [ 125 ] and for medication and psychotherapy sessions [ 59 ].…”
Section: Resultsmentioning
confidence: 99%